Pollen diversity in Brazilian species of Monnina (Polygalaceae) - Leite, Wellerson Picanço; Aguiar-Dias, Ana Cristina Andrade; Fierro-Freire, Alina; Mendonça, Cláudia Barbieri Ferreira; Gonçalves-Esteves, Vania (Phytotaxa, 2015)
Monnina is subordinated to the Polygalaceae family, which consists of 19 genera and approximately 1300 species widely distributed throughout the continents. The current study aims to characterize pollen grains in the genera to provide the basis for their taxonomy. Thus, 13 species were analyzed: subg. Monninopsis (M. insignis and M. malmeana), subg. Pterocayra (M. cardiocarpa, M. cuneata, M. dictyocarpa, M. exalata, M. goiana, M. itapoanensis, M. oblongifolia, M. resedoides, M. richardiana, M. stenophylla, M. tristaniana). The shape of the species widely varied: M. insignis and M. malmeana showed prolate pollen grains; M. cardiocarpa, M. resedoides and M. richardiana showed subprolate pollen grains; and M. itapoanensis, M. stenophylla, and M. tristaniana showed oblate spheroidal and prolate spheroidal pollen grains in most of the species. According to data obtained in the current study, it can be concluded that it is possible to differentiate the species based on pollen attributes. Another important feature in the characterization of the species was the number of apertures, which varied from 10 to19 colporate ones.